Self-direction in adult learning: What we have learned and what we need to know - Ralph G. Brockett; Rosemary S. Caffarella; Lorraine A. Cavaliere; Lucy M. Guglielmino; Carol E. Kasworm; Huey B. Long (Adult Education Research Conference, 1994)
Few research topics in adult education have received more attention that self-direction in learning. It has been nearly 25 years since Tough's (1979) original investigation of the learning projects undertaken by adults. This study, and the numerous replications using the learning projects methodology, offered to the field an understanding of the frequency and nature of learning projects that are self-planned. This line of inquiry served as a foundation for other branches of inquiry into the study of self-direction in learning. Together, these approaches have greatly enhanced our understanding of self-direction. At the same time, some critics have challenged the appropriateness of certain methodological approaches to studying self-direction, while other critics have advocated de-emphasizing this research direction altogether. The purpose of this discussion is to examine research on self-direction in order to address the following questions: 1) How has previous work on self-direction contributed to the development of the future research agenda in this area? And 2) What are some of the promising direction for future research on self-direction? In order to accomplish this, brief discussion will be offered relative to qualitative methods of studying self-direction (Cavaliere), measurement of self-direction in learning (Guglielmino), and emerging theoretical perspectives that can contribute to the future research agenda (Caffarella). In addition, two responses to these developments will be provided (Kasworm and Long).